IDENTIFICATIONTEST OF ANDALIMAN METHANOL EXTRACT STEROID COMPOUNDS (ZANTHOXYLUM ACANTHOPODIUM DC) BY THIN LAYER CHROMATOGRAPHY - Natasya Sabaria Aritonang; Sherlyn Sherlyn; Linda Chiuman; Rudy Rudy (Journal Health & Science : Gorontalo Journal Health and Science Community, 2022)
Andaliman is one of the many spice plants native to North Sumatra and is known to have many benefits as a pain reliever, anti-inflammatory, cough medicine, rheumatism, and back pain. In this study, a series of test was done to  identify for steroid compounds from the fraction of methanol andaliman extract (Zanthoxylum acanthopodium DC) by using thin layer chromatography. This study was designed to determine the presence of terpenoid/steroid compounds in the andaliman (Zanthoxylum acanthopodium DC) extract . Extraction was carried out using by maceration method  using methanol as solvent, followed by phytochemical test and confirmation test using TLC (Thin Layer Chromatography) namely GF254 plate as stationary phase, mixture of n-hexane:ethyl acetate with ratio of 7:3 as mobile phase,the appearance of the stains were carried out on UV with wavelenghts of 254 nm and 366 nm and by spraying Liebermann Burchard reagent as a spot viewer. The results of the phytochemical screening analysis on the Andaliman extract showed that the methanol andaliman extract contained steroid compounds and the TLC analysis showed a blue color, which was the result of a fraction indicating the presence of steroids and a pink color indicating the presence of terpenoids. The smallest terpenoid Rf stain was 0 cm and the highest Rf was 0.92 cm, while the smallest steroid Rf stain was 0 cm and the highest Rf was 0.71cm. Therefore, the Rf value for terpenoids, which is the result of the fraction of ethyl acetate and the Rf value of steroids, which is the result of the fraction of n-hexane and ethyl acetate, has met the requirements for a good Rf value between 0.2 to 0.8.Keywords: Andaliman; Steroids; Fractionation; Thin layer chromatography.                                                                   AbstrakAndaliman merupakan salah satu dari sekian banyak tanaman rempah asli Sumatera Utara dan diketahui memiliki banyak khasiat sebagai pereda nyeri, antiinflamasi, obat batuk, rematik, dan sakit punggung. Pada penelitian ini dilakukan uji identifikasi steroid fraksi metanol andaliman (Zanthoxylum acanthopodium DC) secara kromatografi lapis tipis. Penelitian ini dirancang untuk mengetahui adanya senyawa terpenoid/steroid dalam fraksi ekstrak metanol andaliman (Zanthoxylum acanthopodium DC). Proses ekstraksi dilakukan dengan metode maserasi menggunakan metanol sebagai pelarut, dilanjutkan dengan uji fitokimia dan uji konfirmasi menggunakan KLT (Kromatografi Lapis Tipis) yaitu plat GF254 sebagai fase diam, campuran n-heksan:etil asetat dengan perbandingan 7:3 sebagai fase gerak, penampakan noda dilakukan pada UV dengan panjang gelombang 254 nm dan 366 nm serta dengan penyemprotan pereaksi Lieberman Buchard sebagai penampak bercak. Hasil analisa skrinning fitokimia pada ekstrak andaliman menunjukkan bahwa ekstrak metanol andaliman mengandung senyawa steroid dan pada hasil analisa KLT menunjukkan warna biru yaitu hasil fraksi yang menampakkan adanya steroid dan warna merah muda yang menampakkan adanya terpenoid. Noda Rf  terpenoid terkecil adalah 0 cm dan Rf tertinggi 0,92 cm, sedangkan noda Rf steroid terkecil 0 cm dan Rf terbesar 0,71cm. Oleh karena itu, nilai Rf untuk terpenoid yaitu hasil fraksi dari etil asetat dan nilai Rf steroid yaitu hasil fraksi dari n-heksana dan etil asetat telah memenuhi syarat nilai Rf yang baik adalah di antara 0,2 sampai 0,8.Kata kunci: Andaliman; Steroid; Fraksinasi; Kromatografi Lapis Tipis.